Pemberian Relaksasi Otot Progresif pada Lansia Dengan Hipertensi Essensial di Kota Jambi - Salvita Fitrianti; Miko Eka Putri (Universitas Batanghari Jambi, 2018)
Based on health surveys, 30% of Indonesians are hypertensive. Hypertension is a risk factor for the third-leading cause of death after stroke and tuberculosis, i.e. 67% of the population of deaths at all ages. The number of an elderly female with essential hypertension at the public health center Simpang Kawat Jambi city year 2017 as many as 191 people. This study aimed to determine is there the effect of giving progressive muscle relaxation techniques toward changes in blood pressure in elderly with essential hypertension. This study used one group pre-post test design method; it used simple random sampling technique, numbers of samples were 20 respondents. This study was conducted at Auditorium the public health center Simpang Kawat Jambi city from July 24th – 30th 2017. The instruments are Blood pressure measurement results, data analyzed as univariate and bivariate. The findings indicated that p-value Systole blood pressure p-value = 0.000 and diastole p-value = 0.000, so it can conclude that there is the significant effect of Changes in blood pressure in the elderly with essential hypertension before and after the technique of progressive muscle relaxation at the public health center Simpang Kawat Jambi city. It expected to Health workers can provide knowledge about progressive muscle relaxation technique exercises so that people with essential hypertension can control blood pressure independently at home.